Development and Performance Test of Variable Spray Control System Based on Target Leaf Area Density Parameter - FAN Daoquan; ZHANG Meina; PAN Jian; LYU Xiaolan (智慧农业, 2021)
Variable spray technology is an important means to improve pesticide utilization rate and save pesticide. Fruit tree is a kind of three-dimensional space, and the densities of branches and leaves in the canopy of fruit trees at different locations are different at the same time. The ideal state of spray is to adjust the amount of spray according to local characteristics, so as to realize the application of the spray on the canopy of fruit trees as required and improve the utilization rate of pesticide. In order to achieve the effect of reducing the dosage and increasing the efficiency of pesticide application, a variable spray control system was developed and the methods for computing leaf area density parameter and pulse width modulation(PWM)'s duty ratio of actuators were proposed. As the dosage parameter, the leaf area density was derived based on the point cloud density detected by LiDAR sensor on the upper computer. Then PWM's duty ratio was calculated based on the leaf area density and sent to the slave computer-PLC in real time. The communication between upper and slave computer was carried out through RS485 standard. So the spray flow of each nozzle was controlled by the switching frequency of the solenoid valve with PWM's duty ratio signal. Key parameters were obtained by the test including the net size of spray unit, delay time of the system and the function relationship between the PWM's duty ratio and the spray flow of nozzle. The test results showed that there was a linear relationship between the PWM's duty ratio and the spray flow of nozzle under the pressure of 0.2, 0.3 and 0.4 MPa, and the linear goodness of fit were all above 0.98. Finally, the effectiveness of the variable spray system was verified by the spray test. The test results showed that the minimum number of droplets per unit area (cm2) on the water-sensitive paper was 35 drops at the sampling point, which was higher than the 25 drops defined by the common method for the spray amplitude of aerosol in the air supply spray. Under 39.9% of the canopy ratio between the target canopy area and the whole area, the variable spraying mode saved 71.96% of the pesticide dosage compared with the continuous spraying mode, and 29.72% compared with the target spraying mode, achieving the dose reduction effect.